Explicit and Implicit Own's Body and Space Perception in Painful Musculoskeletal Disorders and Rheumatic Diseases: A Systematic Scoping Review - Viceconti, Antonello; Camerone, Eleonora Maria; Luzzi, Deborah; Pentassuglia, Debora; Pardini, Matteo; Ristori, Diego; Rossettini, Giacomo; Gallace, Alberto; Longo, Matthew R.; Testa, Marco (Frontiers in Human Neuroscience, 2020)
A large body of literature on chronic pain from musculoskeletal disorders and rheumatic diseases has investigated primary somatosensory alterations and their association with cortical changes, leaving the area of somatoperception poorly understood. Explicit and implicit body perception relies on higher-order multisensory integration systems that go beyond simple sensory processing. We systematically mapped the literature published about the topics of: a) somatoperception; b) body ownership; and c) perception of space. The results were organized around the two main topics of the assessment and treatment of perceptual dysfunctions. This scoping review followed the six-stage methodology suggested by Arksey and O’Malley. Ten electronic databases and grey literature were systematically searched. The PRISMA Extension for Scoping Reviews was used for reporting results. Two reviewers with different background, independently performed study screening and selection, and one author performed data extraction, checked by a second reviewer. Thirty-seven studies fulfilled the eligibility criteria. The majority of studies (68%) concerned the assessment methodology, and the remaining 32% investigated the effects of therapeutic interventions. Research designs, methodologies adopted, and settings varied considerably across studies. Evidence of distorted body experience were found mainly for explicit somatoperception, especially in studies adopting self-administered questionnaire and subjective measures, highlighting the presence of sub-groups with different perceptual features in some cases. Almost half of the intervention studies (42%) provided therapeutic approaches combing more than one perceptual task, or sensory-motor task together with perceptual strategies, thus it was difficult to estimate the relative effectiveness of each single therapeutic component. To our knowledge, this is the first attempt to systematically map and summarize this research area in the field of musculoskeletal disorders and rheumatic diseases. Although methodological limitations limit the validity of the evidence obtained, some strategies of assessment tested and therapeutic strategies proposed represent useful starting points for further research. This review highlights preliminary evidence, strengths, and limitations of the literature published about the research questions, identifying questions that remain opened to be addressed, and make suggestions for future research studies. Body representation, as well as pain perception and treatment, can be better understood if an enlarged perspective including body and space perception is considered.